2016
DOI: 10.1053/j.jvca.2016.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Is pulsatile perfusion has significant effects on renal function in patients undergoing cardiac surgery? An observational study

Abstract: Introduction. Radiofrequency (RF) ablation is a well-established alternative treatment for primary and secondary lung tumours (1). It is performed in patients who are deemed unsuitable for, or would prefer not to undergo, surgery (2). At present, there is little data or consensus in the literature describing the anaesthetic management of this high-risk cohort of patients in the immediate perioperative period. Method. We describe a case series from our institution of 100 patients over a period of 5 years (2008-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Milano et al found that patients undergoing pulsatile perfusion CPB during aortic valve replacement had no significant differences in pre vs. postoperative creatine clearance, while a statistically significant difference was observed in patients undergoing normal perfusion ( 122 ). Similar results were found by Natarajan et al ( 124 ). Mohammadzadeh et al found more extensive dysregulation in BUN and creatinine levels in patients undergoing non-pulsatile CPB ( 125 ).…”
Section: Postoperative Vascular Dysfunction and Organ Damage: ...supporting
confidence: 92%
“…Milano et al found that patients undergoing pulsatile perfusion CPB during aortic valve replacement had no significant differences in pre vs. postoperative creatine clearance, while a statistically significant difference was observed in patients undergoing normal perfusion ( 122 ). Similar results were found by Natarajan et al ( 124 ). Mohammadzadeh et al found more extensive dysregulation in BUN and creatinine levels in patients undergoing non-pulsatile CPB ( 125 ).…”
Section: Postoperative Vascular Dysfunction and Organ Damage: ...supporting
confidence: 92%